Analisis Komparasi Kebijakan India dan Indonesia dalam Penanganan Google Tax - Fariz Pradipta Mursyid; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2018)
Taxes are one of the largest sources of state revenue, so the state is vying to optimize itstax revenues. However, there are some companies that make tax avoidance schemes andtax planning aggressively so that the state loses. Google Tax is a tax avoidance methodwith Double Irish and Dutch Sandwich schemes. Indonesia and India are equallydisadvantaged by Google in terms of Taxes, but India has stepped forward with the regimeor law that has been made equalization levy. This study aims to provide an understandingof the formulation of the Google Tax regime in India and Indonesia. Policy MakingTheory is used to analyze the comparison of policies in India and Indonesia whenovercoming Google Tax. This study uses a descriptive-comparative method to explain howthe comparison of Google Tax policy planning in India and Indonesia based on thePolitical will of the policy makers in each country. The result of this research is that thereare similarities and differences of political will which is owned by the decision makers ofthe two countries, where the intention in building the infrastructure, but in Indonesia ishindered by bureaucracy complex.